2016
DOI: 10.1111/ajt.13487
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Donor-Specific HLA Antibody Formation in Two Patients With Crigler-Najjar Syndrome Type I Following Human Hepatocyte Transplantation With Partial Hepatectomy Preconditioning

Abstract: Clinical hepatocyte transplantation is hampered by low engraftment rates and gradual loss of function resulting in incomplete correction of the underlying disease. Preconditioning with partial hepatectomy improves engraftment in animal studies. Our aim was to study safety and efficacy of partial hepatectomy preconditioning in clinical hepatocyte transplantation. Two patients with Crigler‐Najjar syndrome type I underwent liver resection followed by hepatocyte transplantation. A transient increase of hepatocyte … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 23 publications
1
58
0
Order By: Relevance
“…Clinical experience to date with hepatocyte or islet transplant to the liver demonstrate the failure to achieve long-term cellular allograft survival despite the use of conventional immunosuppression. Thus, in contrast to the immunotolerant theory of the liver microenvironment which would predict the need for minimal immunosuppression, the current studies highlight the need to develop more effective immunotherapeutic strategies to target both unique CD8-mediated immune responses primed in the liver and conventional alloimmune rejection pathways 13,17,18,71 .…”
Section: Discussionmentioning
confidence: 95%
“…Clinical experience to date with hepatocyte or islet transplant to the liver demonstrate the failure to achieve long-term cellular allograft survival despite the use of conventional immunosuppression. Thus, in contrast to the immunotolerant theory of the liver microenvironment which would predict the need for minimal immunosuppression, the current studies highlight the need to develop more effective immunotherapeutic strategies to target both unique CD8-mediated immune responses primed in the liver and conventional alloimmune rejection pathways 13,17,18,71 .…”
Section: Discussionmentioning
confidence: 95%
“…Given the importance of AMR in causing acute graft dysfunction 11 and the negative correlation of DSA with long-term allograft survival for both cell and organ transplants 7-9,35-38 , it is of great interest to devise optimal maintenance immunosuppression to suppress the emergence of DSA posttransplant. The clinical literature includes publications which report that no current immunosuppressive regimens effectively prevent the development of DSA 10,11 , while others infer relative efficacy of CNi by reporting that conversion of kidney transplant recipients from CNi to mTORi-based therapy is associated with a negative impact on DSA production and graft survival 19,39-41 .…”
Section: Discussionmentioning
confidence: 99%
“…CNi-based immunotherapies are used following clinical cell transplantation including hepatocyte transplantation but have been associated with limited success for sustained hepatocellular allograft survival 9,58-60 While early studies have not sufficiently explored alloantibody responses following clinical hepatocyte transplant, recently Jorns et al reported the development of de novo donor-specific HLA antibody in 2 patients who underwent hepatocyte transplantation. The onset of humoral alloimmunity and graft loss occurred in the context of lowering and eventual discontinuation of immunosuppression in 1 patient and despite the use of maintenance immunosuppression with CNi and low dose steroids in the second case 9 . The current experimental studies which demonstrate the lack of efficacy of CNi for suppression of alloantibody production provide insight into clinical studies which demonstrate detection of DSA in CNi-treated recipients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The development and contribution of donor-specific antibodies (DSA) in HT is still very much unknown. The presence of de novo DSA following HT has been temporarily associated with graft loss (9, 25) and in one reported case was associated with the peak measurement of the immune reactivity index score that has been shown to enable the prediction rejection (25). Ultimately, a more robust understanding of the immunological responses induced by HT is needed to help guide therapeutic regimens that will enable extended cell graft survival and broader application of HT to patients who will benefit from this promising therapy.…”
Section: Improving Transplanted Hepatocyte Survival and Monitoringmentioning
confidence: 96%